IMPROVING TEACHER PROFESSIONALISM THROUGH IN HOUSE TRAINING MODEL TO HIGHER ORDER THINKING SKILLS ITEMS SMAN 10 REFFERENCE PADANG - Arnellis Arnellis; Elita Zusti Jamaan; Nonong Amalita (Pelita Eksakta, 2019)
This activity of workshop aims to provide an understanding of the way of developing Higher Order Thinking Skill (HOTS) items, provides direct experience in transforming common problems into HOT questions and in developing HOT items for teachers in Senior High School at SMAN 10 Reference Padang. The target is teachers of Senior High School at Padang district who are chosen by five teacher selected from few teachers impact in Senior High School at Padang The Workshop was held on Saturday in a row on September 22th dan 29 th 2018 at SMA 10 Reference Padang, using presentation, discussions, and question and answer about problems associated with development of HOT items. Based on the result, the attitude of activeness, and responsibility to do assignment in a row in the category good, very good. In general, this workshop activity success and on target, proved by the participants who were very enthusiastic in following the activities from beginning until at the end. Hopefully, the participants who attended the activity willing to share their knowledge with other teachers in their impact school